2001
DOI: 10.1002/qj.49712757316
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of extreme European daily precipitation simulated by a global and a regional climate model for present and future climates

Abstract: The intensity and distribution of daily precipitation is predicted to change under scenarios of increased greenhouse gases (GHGs). In this paper, we analyse the ability of HadCM2, a general circulation model (GCM), and a high‐resolution regional climate model (RCM), both developed at the Met Office's Hadley Centre, to simulate extreme daily precipitation by reference to observations. A detailed analysis of daily precipitation is made at two UK grid boxes, where probabilities of reaching daily thresholds in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(61 citation statements)
references
References 12 publications
3
57
0
Order By: Relevance
“…The increase in resolution also improves the simulated temporal variability, including simulation of extremes (Durman et al, 2001). …”
Section: Hadrm3bmentioning
confidence: 97%
“…The increase in resolution also improves the simulated temporal variability, including simulation of extremes (Durman et al, 2001). …”
Section: Hadrm3bmentioning
confidence: 97%
“…For this variable it has been shown that RCMs are able to add significant information to the driving global simulations, both in space and time (e.g., Jones et al 1995;Durman et al 2001;Jones et al 2004). In general terms, the RCMs produce an intensification of precipitation with respect to the driving global climate model (GCM), related to the intensification of the hydrological cycle (Jones et al 1995;Durman et al 2001;Buonomo et al 2007). Lynn et al (2010) tested a regional climate model with different physics components at two different spatial resolutions.…”
Section: Introductionmentioning
confidence: 99%
“…Maraun et al (2010) reviewed the situation with regard to RCM-simulated precipitation. Compared with their driving GCMs, RCMs tend to better reproduce the daily distribution of precipitation, including extreme events, and also spatial features of the field over regions of complex topography (Durman, Gregory, Hassell, Jones, & Murphy, 2001;Frei, Schöll, Fukutome, Schmidli, & Vidale, 2006;Maraun et al, 2010). The characteristic length scale at which the largest improvement in model skill occurs for precipitation tends to be smaller than that for temperature, often not occurring until below 12 km or so (Flato et al, 2013;Maraun et al, 2010).…”
Section: Introductionmentioning
confidence: 95%